Assessment of heavy metal contamination and health risks in groundwater of Abakaliki Metropolis, Nigeria - Andrew A. Tyopine; Nwabueze I. Elom; Folasade Alomaja; Nnadozie Onyezewe; Divine C. Mbah; Blessing Aguma; Chelsey O. Nwoke; Ugochukwu Oraeki (Discover Water)
Abstract This study aimed to assess the human health risks associated with groundwater consumption in Abakaliki Metropolis using Water Quality Index (WQI) and HERisk code. Groundwater samples (n = 32) obtained from boreholes were analysed for pH, Zn, Pb. Fe, Cr and NO3 to evaluate both non-carcinogenic and carcinogenic health risks. The average concentrations of these parameters, except Pb (0.02 mg/L) and Cr (0.06 mg/L), were within permissible limits. The distribution of the average concentrations of the parameters followed the order: Zn > Cr > Fe > NO3 > Pb. The WQI ranged from 0.15 to 505.67 classifying 12.50% of the water samples as excellent sources of drinking water, 9.38% as good, 9.38% as poor, 12.50% as very poor and 56.25% unfit for drinking. The HERisk code revealed significant non-carcinogenic and carcinogenic health risks exceeding safety limits (< 1 × 106–1 × 104), especially for children. A linear regression model showed a relatively strong correlation between WQI and HERisk code (R2 = 0.6824) for oral exposure route, highlighting the potential health hazards of consuming contaminated groundwater. This study has contributed to understanding the health risks posed by heavy metals, particularly Pb and Cr, in Abakaliki Metropolis, guiding future interventions and public health policies.